Development of study skills in the development of school teachers on the basis of public online open courses - Soyibnazarov Abbosjon Ikromjonovich (International Journal on Orange Technologies, 2020)
This article discusses the development of teaching skills in the training of school teachers on the basis of public online open courses. It is no secret that today some teachers of the public education system of Uzbekistan are not able to work freely and independently with modern information technology. Public online open courses are just as relevant for today’s educators as they can independently develop their knowledge without being separated from work. In order to study in such courses, it is necessary to guide them properly and develop their skills.